The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/acm2.12548
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in measurements of linear accelerator output

Abstract: Purpose Seasonal trends in linear accelerator output have been reported by at least one institution and data have suggested that they may be present at our center as well. The purpose of this work was to characterize these trends and determine whether local environmental conditions within the treatment rooms may be impacting the linear accelerators and/or the quality control (QC) dosimeter. Methods Runtime plots of daily output data, acquired using an in‐house ion chamber‐based device, over 3 yr and for 15 lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Output increase per year Pearson et al (2020) [3] 8 Varian TrueBeams 3 years 3-4% Barnes and Greer (2017) [4] 1 Varian TrueBeam 5 months 3% Chan et al (2015) [6] 1 Varian Trilogy 5 years 3% Hossain (2014) [7] 1 Varian Trilogy and 2 iX Varian Linacs 3.5 years 2-4% Uddin (2012) [8] 3 Varian Linacs 4 years 2% Grattan and Hounsell (2011) [9] 4 Varian 2100 C/D 7 years 3% Luketina and Greig (2004) [10] 2 Varian 2100 C/D 5.5 years 2.5% Bartolac et al (2019) [11] 15 Linacs of different makes and models 3 years 2-3% Bolt et al (2018) [13] 27 Varian TrueBeams 6 months 2.1% [16] 8 Linacs of different makes and models 5 years 2% over time). It is known that increasing the output measurement frequency and decreasing the action level help to improve the quality of a radiotherapy treatment [17].…”
Section: Authors Linacs Under Investigation Observation Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Output increase per year Pearson et al (2020) [3] 8 Varian TrueBeams 3 years 3-4% Barnes and Greer (2017) [4] 1 Varian TrueBeam 5 months 3% Chan et al (2015) [6] 1 Varian Trilogy 5 years 3% Hossain (2014) [7] 1 Varian Trilogy and 2 iX Varian Linacs 3.5 years 2-4% Uddin (2012) [8] 3 Varian Linacs 4 years 2% Grattan and Hounsell (2011) [9] 4 Varian 2100 C/D 7 years 3% Luketina and Greig (2004) [10] 2 Varian 2100 C/D 5.5 years 2.5% Bartolac et al (2019) [11] 15 Linacs of different makes and models 3 years 2-3% Bolt et al (2018) [13] 27 Varian TrueBeams 6 months 2.1% [16] 8 Linacs of different makes and models 5 years 2% over time). It is known that increasing the output measurement frequency and decreasing the action level help to improve the quality of a radiotherapy treatment [17].…”
Section: Authors Linacs Under Investigation Observation Periodmentioning
confidence: 99%
“…It is reported that the Linacs output does not remain constant over time but shows significant changes during the course of a year [3]- [9] and even seasonal variations [7,11], that must be corrected to keep output within the established tolerance limits. The recommended tolerances for daily and monthly output constancy checks are typically ±3% and ±2%, respectively [12], although a more restrictive limit is generally applied to daily tests executed with MPC [3,4].…”
Section: Introductionmentioning
confidence: 99%